KEDUDUKAN AKAD QARDH DALAM REGULASI PERBANKAN SYARIAH: IMPLIKASINYA TERHADAP INOVASI PRODUK - Izazi Nurjaman, Muhamad (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
The understanding that an increase in the loan amount based on a qardh contract constitutes usury is inherent in some communities. In the Islamic banking operational system, this is strictly avoided. However, in various product developments, sharia banks still use the qardh contract. This gives rise to the view from some people that the operational system of Islamic banks is the same as conventional banks, especially since the funds used in product development are customer funds which should be managed for other things that can generate profits. The aim of this research is to analyze the position of qardh contracts in product development in sharia banking. This article uses a normative juridical approach with data analysis techniques which consist of several stages such as reducing data, presenting data and also providing conclusions. The results of this research reveal that the position of the qardh contract in product development using customer funds as in the DSN/MUI fatwa Number 79 of 2011 concerning qardh using customer funds is only limited to a complementary contract to the mu 'awadhat contract with the aim of seeking profit. So that the profits of sharia banks come from the mu 'awadhat contract, not from the qardh contract carried out.